2012
DOI: 10.5539/jas.v5n1p154
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality Characteristics and Effect of Mating Ratio on Reproductive Performance of Hubbard Broiler Breeders

Abstract: A study was conducted at the National Animal Production Research Institute (NAPRI) Shika, Zaria, Nigeria to access some semen quality characteristics and to determine the effect of mating ratio on fertility and hatchability of Hubbard broiler breeders. 20 cocks were examined for semen quality characteristics. Parameters evaluated were: ejaculate volume, semen pH, sperm concentration and sperm motility. Sequel to semen quality evaluation, hens were divided into three groups according to mating ratio (cock to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…These results corroborate with those observed by Rybnick, Horbanczuk, Naranowicz, Lukaszewicz, and Malecki (2007), Modupe, Livinus, & Ifeanyi (2013) and Bezerra et al (2016), who verified semen pH values between 6.4 and 8.0; where they also affirm that the use of lipid sources in diets for cocks directly influences semen pH and, consequently, sperm performance and viability, in which a basic pH is considered ideal for the maintenance of spermatozoa activity.…”
Section: Resultssupporting
confidence: 81%
“…These results corroborate with those observed by Rybnick, Horbanczuk, Naranowicz, Lukaszewicz, and Malecki (2007), Modupe, Livinus, & Ifeanyi (2013) and Bezerra et al (2016), who verified semen pH values between 6.4 and 8.0; where they also affirm that the use of lipid sources in diets for cocks directly influences semen pH and, consequently, sperm performance and viability, in which a basic pH is considered ideal for the maintenance of spermatozoa activity.…”
Section: Resultssupporting
confidence: 81%
“…Semen of broilers has been shown to be alkaline (Orunmuyi et al 2013), and in this study, the best sperm movement status was observed at pH 7.5 and 8.0 by comprehensive consideration of sperm motility, sperm velocity and sperm movement trajectory. So, the weakly alkaline environment with a pH close to semen pH is suitable to assess the sperm motility parameters of Tree Sparrow.…”
Section: Discussionmentioning
confidence: 67%
“…The right seminal glomus of 8 males brought back to the laboratory and euthanized in 2017 was removed and cut in half in 0.5 mL of HBSS, which could keep the sperm concentration between 2 and 50 × 10 6 sperm/mL (the recommended concentration for sperm motility parameters assessment in WHO laboratory manual for the examination and processing of human semen). The preheated temperature of HBSS was set to 40 °C (the body temperature of Tree Sparrows), and the pH was set to 7.5 (according to the semen pH of poultry) (Orunmuyi et al 2013) and because weak alkaline pH has shown increased sperm movement (Holm and Wishart 1998). Next, a 10-μL sperm suspension was used for the assessment of the sperm motility parameters by the WLJY-9000 CASA system at 3, 5, 15, 20, and 30 min after dilution.…”
Section: Effect Of Time Since Dilution and Until Analysis On Sperm Momentioning
confidence: 99%
See 1 more Smart Citation
“…Telur yang terkumpul kemudian dilakukan tahap penetasan pada suhu 37,5º-38°C dan kelembaban 60-65% (Boleli et al, 2016;Addo et al, 2018). Candling dilakukan pada penetasan hari ke-7 untuk mengetahui fertilitas telur Fertilitas telur sesuai acuan Modupe et al (2013); Mohan et al (2015), Fikremariam dan Tilahun, (2016) bahwa persentase fertilitas sebagai rasio jumlah telur fertil terhadap jumlah total telur yang masukkan pada mesin tetas.…”
Section: Penetasanunclassified